(untitled) (Bangladesh Journal of Zoology, 2021)
The Bangladeshi reef fish species have not been studied thoroughly. An attempt has been made for taxonomic identification of coral-associated fish through morphological studies. Mostly dead and few live fishes were collected from local fishermen, fish landing zone, and fish markets in St. Martin’s Island, Bay of Bengal, Bangladesh, from October 2015 to July 2016, visiting seven times. Samples were also obtained from local boys who collected fishes by using hook and line. The study recorded the first occurrence of 16 coral-associated fish species such as Caesio cuning, Lethrinus ornatus, Upeneus suahelicus, Upeneus asymmetricus, Scarus taeniopterus, Scarus zufar, Bodianus neilli, Parapercis clathrata, Parapercis diplospilus, Pomadasys furcatus, Siganus fuscescens, Acanthopagrus berda, Gerres erythrourus, Lagocephalus spadiceus, Psettodes bennettii, and Heteroconger perissodon. Among them, Parapercis clathrata, Parapercis diplospilus belongs to the family Pinguipedidae before, no species was recorded under this family from Bangladesh and a rare and endemic species, Scarus zufar, of the Arabian Sea off Dhofar (Zufar), Oman in the Western Indian Ocean, was recorded for the first time in the Northern Indian Ocean in the northeastern part of Bay of Bengal. This study increased the number of coral-associated fish from 240 to 256 species and the number of families from 54 to 55 in the coral reef ecosystem of the Bay of Bengal, Bangladesh. Bangladesh J. Zool. 48(2): 263-288, 2020